Psycholinguistic Markers of Personality’s Life Roles - Odintsova, Anastasiia (East European Journal of Psycholinguistics, 2014)
The present paper is focused on the study of how individual speech and leading life role are related. The research envisaged, firstly, a definition of the ‘personality life role’ concept, and its substantiation. Secondly, psychological features of the defined roles that embraced individual motivational, behavioral, intellectual, and emotional qualities, were defined. A factor analysis showed that ‘active group’ individuals tended to be more practical and persistent in attaining their goals. Among the most prominent features of the young people having consecutive, semantic, and awareness life roles were emotional responsiveness, tense, conformity, high behavior self-control, and low intelligence indices. However, the individuals with axiological and semantic life roles were more friendly, optimistic, straightforward, possessed human resources managing skills. On the third stage of the study, which involved a method of narrative analysis, a set of psycholinguistic markers typical for the individuals of each life role group was established. References Abulkhanova-Slavskaya, K. A. (1991). Strategija zhizni [Strategy of Life]. Moscow: Smysl. Biddle, B. J., Thomas, E. J. (1966). Role Theory: Concepts and Research. N. Y.: Wiley & Sons. Ulanovich O. I. (2010). Psikholingvistika [Psycholinguistics]. Minsk: Grivtsova Publishers.